Nanomaterials: Invisible Structures, Visible Performances - Ng, Rashida (ARCC Conference Repository, 2013)
Nanotechnology is the study and manipulation of matter at the molecular or subatomic scale. Advancements in this diverse and vast field of science are rapidly producing innovative materials andprocesses with a wide range of applications. Despite the diminutive scale of nanotechnology, the influenceof the field is far reaching and is poised to exert a profound effect on the built environment. Beyond selfcleaning surfaces and anti-fog coatings, nanotechnology suggests an extension of the scalar range at which architecture operates. Challenging its modes of fabrication, emerging research within this micro-science confronts energy intensive modes of material production in favor of ostensibly effortless processes thatemulate nature. This paper considers the potential for research in the growing field of nanotechnology to instigate a new generation of performative materials made possible through the design of customized molecular structures that remain veiled from the naked human eye. Through a review of current nanotechnology research, it queries a series of shared principles between science and design in an attempt to identify productive areas for future collaborative research in architecture. Furthermore, it confronts the premise of visibility of research through the exploration of a state of materiality that is naturally imperceptible in its formal organization, yet strikingly conspicuous in its active and situated processes.